Pengaruh Beban Pajak Tangguhan, Tax Planning dan Tax Avoidance Terhadap Manajemen Laba Dengan GCG Sebagai Pemoderasi - Harry Budiantoro; Devi Nur Fazriyani; Perdana Wahyu Santosa; Alyta Shabrina Zhusryn; Kanaya Lapae (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this research is to determine the impact of Deferred Tax Burden, Tax Planning, and Tax Avoidance on Earnings Management in the context of Good Corporate Governance Moderation. This is a quantitative study, with secondary data obtained from the Indonesia Stock Exchange as the data source (IDX). This study's population consists of industrial companies that are listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020. Purposive sampling was used in this study, with a sample of 19 companies. Multiple linear regression analysis is used in this study. According to the findings of this study, deferred tax expense, tax planning, and tax avoidance have no effect on earnings management, either partially or simultaneously. Furthermore, Good Corporate Governance with the proxy of the Independent Commissioner is unable to moderate the relationship between Deferred Tax Burden, Tax Planning, and Tax Avoidance on Earnings Management